In vitro assessment of chemical surface treatments on the shear bond strength of metal orthodontic brackets to CAD/CAM provisional materials - Alzaid, Abdulaziz A.; Alanazi, Khalid K.; Alharbi, Maha N.; Alyahya, Lulu A.; Alqarni, Hatem; Alsaloum, Mohammed; Alfallaj, Hayam; Alotaibi, Ghada S. (Frontiers in Dental Medicine, 2024)
The growing demand for orthodontic treatment in patients irrespective of age highlights the need for effective bonding of brackets to provisional crowns (PCs).This study evaluates the shear bond strength (SBS) of orthodontic brackets to 3D-printed and milled PC materials, comparing the effects of hydrofluoric acid (HFA) and phosphoric acid (PA) etching.Materials and methods: Forty cylinders were fabricated using a 3D printer with hybrid resin, and forty were milled from cross-linked polymethyl methacrylate (PMMA) resin.Stainless steel brackets were bonded with light-cured composite resin. Twenty specimens from each group were treated with 9.5% HFA, while the rest of the specimens received 37% PA. Post-bonding, specimens underwent thermocycling and were examined with SEM. SBS testing followed ISO/TS 11405-2015 guidelines. The failure patterns and bond interface were assessed by the Adhesive Remnant Index (ARI) and scanning electron microscopy (SEM).Data was analyzed using ANOVA, Tukey's test,.Results: In 3D-printed materials, HFA etching yielded a significantly higher bond strength (12.59 ± 2.64 MPa) than PA etching (7.77 ± 0.83 MPa). The bond strength was inferior in milled materials: HFA (5.98 ± 0.59 MPa) and PA (5.66 ± 0.65 MPa) with no significant difference between both surface treatments. When each material was evaluated separately, a significant difference in SBS was found for surface treatments in 3D-printed materials (p < 0.001) but not for milled materials (p = 0.916). ARI scores showed greater adhesive retention in 3D-printed specimens, particularly those treated with HFA. SEM revealed smoother surfaces in 3D-printed specimens compared to rougher surfaces in milled specimens.HFA etching improves SBS in 3D-printed PC, while in milled materials, the choice of etching agent has minimal effect.